Characterizing the myeloid and lymphoid immune response in a porcine model of pulmonary ischemia-reperfusion injury through flow cytometry - Allen Duong; Andrea Mariscal; Lindsay Caldarone; Chun Xu; Lei Huang; Rayoun Ramendra; Shaf Keshavjee; Mingyao Liu; Stephen Juvet; Tereza Martinu (PLoS ONE, 2026)
Pulmonary ischemia-reperfusion injury (IRI) is a major cause of primary graft dysfunction in lung transplantation. Porcine models better simulate physiological conditions and are important for pre-clinical studies; however, comprehensive immune assessment of porcine lungs in IRI has not been performed. We aimed to evaluate immune cells and activation states in porcine IRI models and hypothesized that myeloid and lymphoid cells would infiltrate and activate following IRI. Two sets of porcine orthotopic lung transplants were performed: a 4 h reperfusion (n = 7) and a 72 h survival model (n = 6). Both were compared to a control group without lung injury (n = 6). Lung samples were processed into single cell suspensions and cryopreserved. Thawed samples were stained with anti-porcine antibodies and analyzed by flow cytometry. Absolute counts of neutrophils and CD14 + monocytes increased in the allograft at 4 h and remained stable over 72 h post-transplant. CD14 - CD163 + monocytes and conventional dendritic cells continued to increase by 72 h post-transplant. Lymphoid cell numbers were unchanged overall, but T cells showed increased CD25 expression and a memory phenotype at 4 h. Our analysis revealed early myeloid cell infiltration post-IRI which developed into increased inflammatory and antigen-presenting cell populations by 72 h post-transplant. A transient rise in T cell activation markers was noted, consistent with rodent models. Our findings contribute to our understanding of immunological events in porcine pulmonary IRI, a model that better mimics the clinical setting. Our flow cytometry panels allow for improved immunologic analyses of porcine models in preclinical transplantation research.